PSYCHOLOGICAL ASPECTS OF DIABETES MELLITUS: THE INFLUENCE OF PSYCHO-EMOTIONAL FACTORS ON THE OCCURRENCE, COURSE AND COMPENSATION OF THE DISEASE - Нарметова Юлдуз Каримовна; Жалилова Маржона Музаффаровна (Modern American Journals, 2025)
Diabetes mellitus is a chronic systemic disease in which psycho-emotional factors have a significant impact on the formation of the clinical picture, the dynamics of metabolic disorders and the patient's ability to maintain compensation for carbohydrate metabolism. The article examines in detail the personality traits of patients, emotional disorders, mechanisms of psychosomatic influence on the regulatory systems of the body, as well as specific reactions to the disease. Special Attention is paid to depressive and anxiety states, which are several times more common among diabetic patients compared to the healthy population and significantly worsen the prognosis of the disease. The mechanisms of psychological maladaptation, behavioral features associated with impaired self-regulation, which reduce motivation to comply with treatment, and the influence of alexithymia on the ability to perceive body signals, which makes it difficult to maintain compensation, are described. In the final part of the article, modern methods of psychological correction are considered, including psychotherapeutic strategies, emotional learning, cognitive behavioral approaches, methods for improving the quality of life and building a sustainable system of self-control.
Keywords: Diabetes, psychology, psychosomatics, depression, anxiety, personality, adaptation, self-control, motivation, quality of life.